Biopolitical other - Petrović, Duško (Array, 2011)
In the beginning of this short tex t, which will discuss the question of the postmodern Other, I will propose that the post-Other, or Other in the postmodern condition, be called the biopolitical Other. The thesis is as follows: when we think about the question of the Other in the contemporary condition, which for want of a better definition and following Ly otard could be named postmodern, the dominance of the biopolitical Other can be observed on a global scale.